Analisis Pencapaian Kinerja Keuangan Bank Syariah Indonesia Dan Bank Muamalat Dalam Indeks Maqashid Syariah - Amalia Febi Cahyani; Elsa Okta Akila; Febiola Valentry; Hayatun Nisa; Ersi Sisdianto (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
The purpose of writing this analysis is to investigate the financial performance achievements of Bank Syariah Indonesia (BSI) and Bank Muamalat in the Maqashid Syariah Index, with a focus on profitability, liquidity, asset growth, operational efficiency and sustainable service. The research method used is a literature study, which involves collecting and analyzing data from various relevant and reliable literature sources, including public financial reports, academic books, scientific journals, and other official documents. The research results show that both banks have demonstrated a strong commitment to sharia principles in their operations, with adequate performance in key aspects such as profitability, liquidity, asset growth, operational efficiency and sustainable service. Thus, this analysis provides an in-depth understanding of the contribution of BSI and Bank Muamalat to a sharia-based economy and achieving sharia goals in a broader context.